Rhabdomyolysis associated acute renal failure – Report of two fatal cases and a brief review of literature. (April 2020) - Das, Siddhartha; Hanuman, Srinivas Bheemanathi; Mylapalli, Jhansi Lakshmi
Abstract: Background: Rhabdomyolysis is a potentially fatal condition which occurs due to skeletal muscle injury and classically presents with myalgia and red-brown coloured urine. Presence of excess myoglobin in the glomerular filtrate forms myoglobin casts which causes severe obstruction and necrosis of the tubules leading to acute renal failure. Methods: We report two fatal cases of rhabdomyolysis associated acute renal failure. The first victim died in police custody and the second victim died due to severe physical exertion. Results: In both the cases, creatine kinase levels were elevated and myoglobin was detected in urine in the second case. Myoglobin immunohistochemistry detected the presence of myoglobin cast in the glomerular tubules of kidney in both the cases. Conclusions: Myoglobin immunohistochemistry of renal tissues, serum creatine kinase, urine myoglobin analysis and muscle histopathology are the laboratory tests that should be considered at autopsy where rhabdomyolysis is suspected. Highlights: Two cases of rhabdomyolysis following blunt trauma and severe exertion respectively. Cause of death was acute renal failure in both the cases. Myoglobin IHC of renal tissues using Perl's stain was negative in both the cases. Cases highlight the importance of post-mortem biochemistry and biopsy examination.